STUDENTS' PREFERENCES IN LANGUAGE LEARNING STRATEGY BASED ON GENDER ROLES - Bahing, Bahing; Misrita, Misrita; Aslamiyah, Suaibatul (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2025)
This study explores the impact of gender roles on the use of language learning strategies among English as a Foreign Language (EFL) students. The research addresses two main questions: 1) How do gender roles influence language learning strategies? and 2) What are the students' preferences in the use of these strategies? The study employs a descriptive qualitative methodology, incorporating interviews, classroom observations, and questionnaires to gather data. The research findings reveal significant differences in the language learning strategies employed by male and female students. These differences are analyzed in relation to psychological factors, as discussed by Zoltán Dörnyei. The data reduction process, guided by Miles and Huberman's framework, includes condensation, data display, and conclusion drawing and verification. The analysis shows that while male students tend to favor more competitive and autonomous learning strategies, female students often prefer collaborative and communicative approaches. Additionally, the study highlights the role of cultural and social expectations in shaping these preferences. This research contributes to a deeper understanding of the intricate relationship between gender and language learning strategies, offering insights that can inform teaching practices and curriculum development. By examining the specific needs and preferences of male and female EFL students, educators can develop more effective, inclusive, and supportive language learning environments.